FACING THE CHALLENGES OF ISLAMOPHOBIA: A Study on The Message of Peace in The Qur'an Through the Ma’na cum Maghza Approach - Mahmud, Basri; Imran, Muhammad; Hardivizon, Hardivizon; Husain, Muhammad Zakir (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to uncover the messages of peace in the Qur'an using the ma’na cum maghza approach and analyze their application in addressing the challenges of islamophobia in the modern era. The research employs thematic tafsīr analysis using a qualitative approach, focusing on verses that convey messages of peace, such as al-Baqarah (2:256), al-Mumtaḥanah (60:8), and al-Anfāl (8:61). These verses are examined based on their literal meanings and universal values relevant to the contemporary context. The findings reveal that the Qur'anic messages consistently emphasize the values of tolerance, justice, and peace, which can serve as a foundation for countering negative stereotypes about Islam. The ma’na cum maghza approach enables a deep and practical interpretation of these verses, particularly in the fields of education, media, and global diplomacy. The study also identifies practical strategies for Muslim communities to proactively address islamophobia, such as promoting positive narratives in the media and developing curricula based on Qur'anic values. The study concludes that the Qur'an's messages of peace are not only relevant in the context of islamophobia but also contribute to efforts to build social harmony and global peace. The novelty of this research lies in the use of the ma’na cum maghza approach to contextually elaborate the Qur’anic messages of peace in response to islamophobia—an area that has received limited attention in previous studies.